Women in Lodges and Their Duties in the 19th Century Based on Archives - Serpil Özcan (İslam Tetkikleri Dergisi)
Sufism has been familiar to Anatolians for a long time as a worldview and way of life. The main research topic is the presence of women and their dutiesin Sufi lodges. Therefore, this study shows based on archival documents whether women were found in dervish lodges, what their purpose there was, whether they had duties and, if so, what tasks they carried out, whether they were paid for these duties, and the extent to which they took part in the important decisions of dervish lodges. The number of women in the lodges was determined based on a population register made in the 19th century, and this information was then strengthened with documents from other periods. In this context, the duties of women living in dervish lodges in different periods were determined by scanning the edicts, arzuhal [petitions], and Meclis-i Meşâyih [the establishment in charge of governing lodges] notebooks. As a result of examining these documents, women were revealed to exist who carried out the duties of tekkenişîn [lodge resident], zâviyenişîn [hermitage lodge resident], duagû [reader of prayers], mütevellî [fiduciary], and sheikhs. Women were found who were also observed to receive a salary and benefit from dervish lodges in return for their duties.